Investigations on Improving the Compressive Strength of Sand Column with Cement Grout and Chemical Admixture - et. al., M. Samuel Thanaraj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Grouting is one of the most commonly adopted technique for soil improvement and strengthening. Adding super plasticizers, accelerators, antifreezes, air entraining agent improves the performance of the cement grout. The performance of the grout while injecting in the sand column mainly depends on its fluidity property. Keeping it in mind about the water cement ratio, the strength of the sand column is studied in two sets of experiments one by sand column with cement grout only and another set by sand column with cement grout added with super plasticizers by varying the water cement ratios. Strength parameters like angle of internal friction and cohesion were obtained be direct shear test and unconfined compressive strength test on the specimens by varying the water content. An increase of 15.2kPa to 60.33 kPa was observed in the cohesion value for specimens with 10% water content and 13.8 kpa to 47.2kPa cohesion value observed in the specimens with 20% water content. The angle of internal friction was decreased from 360 to 160 for 10% water content whereas 300 to 100 for 20% water content. A series of experiments were conducted on the sand column grouted with cement and for different water cement ratios as 1.5, 2.0 and 2.5. Another set of experiments were repeated by adding 2%super plasticizer Sulphonated Melamine Formaldehyde (SMF). The experiment results revealed that at lower water cement ratio higher value of compressive strength was observed. It was also observed that the strength increases with curing period.